The Role of Habitat Types and Soil Physicochemical Properties in the Spread of a Non Native Shrub Lantana Camara in the Doon Valley, Western Himalaya, India - Mandal, Gautam; Prasad Joshi, Shambhu (Journal of Environmental Geography, 2014)
Invasive alien species colonize very aggressively and forcefully, menacing native biodiversity. The success of invasive alien plants is due to their opportunistic exploitation of anthropogenic disturbances, the absence of natural enemies, free from herbivory and frequently their allelopathic competition. Invasive species can have a significant impact on development, affecting sustainability of livelihood, food security and essential ecosystem services and dynamics. Lantana camara is a documented weed of worldwide significance; it is indigestible due to its toxic chemicals and highly competitive. In this study physicochemical properties of soil were analysed from different high and low Lantana infested areas. Significant site effect was frequently observed than effect due to invasion status. The present study tested the impact of soil properties in the measured and calculated attributes of Lantana by randomly sampling soil from the highly invaded and less invaded sites in different habitats using the Modified Whittaker plot design. Results indicated that edaphic factors such as soil pH, total nitrogen, soil organic carbon, phosphorus and potassium content positively influenced the growth of Lantana and helped in its own further invasion process. These factors were also positively influencing the measured and calculated attributes of Lantana such as canopy coverage, average crown diameter, shrub canopy area, phytovolume and biomass from all sites. However some attributes like shrub height and stem diameter were negatively influenced by these soil factors. The present results show that Lantana invasion can significantly improve the soil nutrient level but also positively increasing the chances of its further invasion with more copious plant attributes.